Vigilância Epidemiológica da Síndrome Inflamatória Multissistêmica Pediátrica no Estado de São Paulo - Castells Fontes Lourenço, Neisa; Tiemi Masuda, Eliana; Marques Ferreira, Patrícia; Oliveira Messias, Margareth; Frugis Yu, Ana Lúcia Frugis Yu; Marques Pinto Carvalhanas, Telma Regina (BEPA. Boletim Epidemiológico Paulista, 2020)